Challenges and Measures to Counteract Passport Data Falsification in Indonesian Migrant Workers: A Review of the Circular Letter of the Director General of Immigration of the Republic of Indonesia Number: IMI-GR.01.01-0252 of 2023 - Ari Arianto; Muhammad Sya’roni Rofii (Publikasi Indonesia, 2024)
The phenomenon of passport ownership with false data by Indonesian Migrant Workers who are working abroad is a problem that is difficult to eliminate, because there are still many prospective workers who think that the bureaucracy of making passports is difficult. The purpose of this study is to identify the challenges and countermeasures against passport data falsification in Indonesian Migrant Workers, through a review of the Circular Letter of the Director General of Immigration of the Republic of Indonesia Number: IMI-GR.01.01-0252 Year 2023. This research uses a qualitative secondary research approach that allows a researcher to compare other researchers' perspectives on the same case, in order to provide additional understanding. The research findings show that there are still many Indonesian Migrant Workers who are not aware of the dangers that may arise from using passports with fake identities, from being exposed to legal problems, losing their employment rights, to the threat of not being recognized for their citizenship status. In the conclusion, this research found that although the Directorate General of Immigration tries to use more persuasive regulations, these efforts also need to be accompanied by the application of immigration control functions as a form of prevention in preventing the increase of non-procedural Indonesian Migrant Workers.